Nadzór policyjny prowadzony przez Państwową Inspekcję Sanitarną w związku z naruszeniem obowiązku rejestracji substancji chemicznej zgodnie z REACH - Czesak, Joanna; Siwik, Lidia (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the paper entitled Police supervision carried out by the State Sanitary Inspection in connection with the failure to fulfil the chemicals registration obligation according to REACH, the author touches upon the issues connected with supervision activities of the State Sanitary Inspection with respect to fulfilling the chemicals registration obligation. The aim of this paper is to analyse the rules of law in Regulation EC No. 1907/2006 of the European Parliament and of the Council of 18 December 2006 concerning the Registration, Evaluation, Authorisation and Restriction of Chemicals REACH, establishing the European Chemicals Agency, and the national law especially the State Sanitary Inspection Act of 14 March 1985 with respect to evaluating the fulfilment of the chemicals registration obligation. In the conclusion, it is stressed that the discussed obligation results directly from the European Union law and its fulfilment is verified on the basis of the national law. The police supervision consists of three stages: control, decision and enforcement. When issuing a decision as part of this supervision, a body of the State Sanitary Inspection determines authoritatively the legal situation of a chemical manufacturer or importer.
Keywords: Państwowa Inspekcja Sanitarna; nadzór; rejestracja chemikaliów; Europejska Agencja Chemikaliów; policja handlowa; REACH